2013
DOI: 10.1089/dia.2013.0046
|View full text |Cite
|
Sign up to set email alerts
|

Nateglinide and Acarbose Are Comparably Effective Reducers of Postprandial Glycemic Excursions in Chinese Antihyperglycemic Agent–Naive Subjects with Type 2 Diabetes

Abstract: Background: Recent studies have identified postprandial glycemic excursions as risk factors for diabetes complications. This study aimed to compare the effects of nateglinide and acarbose treatments on postprandial glycemic excursions in Chinese subjects with type 2 diabetes. Subjects and Methods: This was a multicenter, open-label, randomized, active-controlled, parallel-group study. One hundred three antihyperglycemic agent-naive subjects with type 2 diabetes (hemoglobin A1c range, 6.5-9.0%) were prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…The novel finding of our study, however, is the positive effect of acarbose on glycemic variability when added to metformin and vildagliptin therapy. Our results are in line with the findings of a study in which 103 antihyperglycemic agent–naive patients with type 2 diabetes were prospectively randomized to nateglinide 120 mg 3 times/day or acarbose 50 mg 3 times/day for 2 weeks . Both agents caused significant reductions on the incremental AUC of the postprandial glucose level and the incremental glucose level peak.…”
Section: Discussionsupporting
confidence: 89%
“…The novel finding of our study, however, is the positive effect of acarbose on glycemic variability when added to metformin and vildagliptin therapy. Our results are in line with the findings of a study in which 103 antihyperglycemic agent–naive patients with type 2 diabetes were prospectively randomized to nateglinide 120 mg 3 times/day or acarbose 50 mg 3 times/day for 2 weeks . Both agents caused significant reductions on the incremental AUC of the postprandial glucose level and the incremental glucose level peak.…”
Section: Discussionsupporting
confidence: 89%
“…Several short-term (2–9 weeks) studies in the People’s Republic of China have confirmed that acarbose exerts similar hypoglycemic effects as nateglinide, particularly on postprandial glucose,2729 although there were obvious differences in the mechanism of action of the two drugs. Nateglinide is an insulinotropic agent that exerts effects on β-cells to enhance early-phase insulin secretion 30,31.…”
Section: Therapeutic Efficacymentioning
confidence: 98%
“…8 The study protocol was designed in accordance with the principles of the Helsinki Declaration II and carried out with pre-approval by the Independent Ethics Committee of Shanghai Jiao Tong University Affiliated Sixth People's Hospital (Shanghai, People's Republic of China). All study participants provided written informed consent.…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
“…The treatment strategy has been illustrated in our previous study. 8 Anthropometric and biochemical measurements Upon enrollment, blood pressure was measured in triplicate using a standard mercury sphygmomanometer, and the average measurement was recorded. Body mass index was calculated as weight (in kg)/height (in m) 2 .…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
See 1 more Smart Citation